ANALISIS KOMPARATIF PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium Cepa L. Aggregatum) BERDASARKAN UKURAN BAHAN TANAM - Wahyuni, Ari; Cintaning, Anis Bias; Nabila, Diah Ayu; Neti, Natali; Sinaga, Tamara Rudang Astari; Wentasari, Risa; Taisa, Rianida; Karmaita, Yummama; Suhartanto, Mohamad Rahmad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Shallot development faces an obstacle, specifically the availability of quality seeds. Onion propagation is usually done conventionally with vegetative propagation methods using bulbs as seeds. The aims of study were to determine the effect of the size of the shallot bulb planting material on the growth and production of shallots, to obtain the variables used in selecting the size of the shallot bulbs.The research was conducted at Leuwikopo Experimental Farm in Dramaga, Bogor from February to May 2024. The experiment was conducted by comparing two treatments and each treatment was repeated 9 times. The treatment used was bulb size, especially large and small. The data obtained were tested using the t-student test at the 5% α level, which compares the results of observations between large and small bulbs. The variable observed consisted of plant height, number of shoots, number of leaves, number of bulbs, number of multiplications, wet weight, and dry weight of bulbs. The results showed that different sizes of bulbs used as shallot plant propagation materials affect the growth and production of shallots. Shallot seeds with large bulb sizes produce better growth than small bulbs. The size of large and small bulbs produces output in the form of variable of the number of bulbs per clump, and wet and dry weights of bulbs that are not different. The variables number of leaves, number of shoots, dry bulb weight, and multiplication rate can be used as characteristics for selecting bulb size.